STOCK PRICE DETERMINANTS AND IMPLICATIONS ON COMPANY VALUE (A STUDY OF THE LQ45 STOCK GROUP CONSISTENTLY LISTED ON THE INDONESIA STOCK EXCHANGE 2011-2022) - Tahmat Tahmat; Jaja Suteja (PT. Altin Riset Publishing, 2025)
The study aims to determine the effect of Debt to Equity, Debt to Assets, Return on Equity and Earning Per Share, inflation, BI Rate interest rates, economic growth, rupiah exchange rates and world oil and their effect on stock prices and the effect of stock prices on company value in the LQ45 stock group listed consistently on the Indonesia Stock Exchange in 2011-2022. The method used in the study is the verification method. The sample in this study was 15 companies, selected by purposive sampling method. Data analysis used panel data analysis techniques. In general, this study concludes that internal factors partially: Debt to Equity and Debt to Assets have a negative and significant effect on stock prices, Return on Equity has a positive and significant effect on stock prices, EPS has a positive but not significant effect on stock prices. While external factors partially: Inflation, Interest Rates, World Oil and Dummy Covid-19 have a negative and significant effect on stock prices, Economic Growth and have no effect on stock prices, Rupiah exchange rate has a positive and significant effect on stock prices. Simultaneously, internal and external factors influence stock prices. Then, stock prices have a positive and significant influence on company value.